Polymer packaging of I2 producing pyrotechnic biocides. Issue 4 (2nd October 2018) - Oxley, J. C.; Smith, J. L.; Porter, M. M.; Brady, J. E.; Levine, R. M.
ABSTRACT: Finding a straightforward counter to infectious biological agents, such as Bacillus anthracis, is of great interest. We have found that a pyrotechnic mixture of iodate salts and aluminum is highly effective at producing heat and elemental iodine, both of which are considered as effective biocides. What is required is a general method of application. This paper outlines an approach to creating sprayable pyrotechnics. Polyurethane foams (energetic and non-energetic), nitrocellulose, and glycidyl azide polymer (GAP) have been applied as binders to pyrotechnic mixtures. Heat produced upon burning these formulations was quantified by bomb calorimetry, while iodine output was quantified by ultraviolet-visible spectroscopy (UV-Vis). The nitrocellulose-pyrotechnic formulation in acetone created a sprayable matrix, which dried to paint-like consistency. While the polyurethane-pyrotechnic was also sprayable, it was dried to a rigid, flammable foam. Properly formulated, all produced significant heat and iodine even under inert atmosphere.